Psychobiosocial experiences in sport: Development and initial validation of a semantic differential scale. (July 2021) - Robazza, Claudio; Ruiz, Montse C.; Bortoli, Laura
Abstract: Objectives: To develop and validate the Psychobiosocial Experience Semantic Differential scale in sport (PESD-Sport), a new measure to assess discrete emotions and performance-related experiences in sport as conceptualized within the individual zones of optimal functioning (IZOF; Hanin, 2000, 2007, 2010) framework. Method: In Study 1, we developed a preliminary 53-item version of the scale using a semantic differential format in the construction of the items pertaining to 12 psychobiosocial modalities. We chose this format to attain a clear representation of psychobiosocial states between opposites along perceived performance functionality (i.e., functional, dysfunctional). The preliminary scale was then administered in a sample of 280 athletes. In Study 2, a 30-item scale derived from Study 1 was cross validated in a second independent sample of 302 athletes. Results: Findings from Study 1 provided preliminary evidence of factorial and construct validity for a 10-modality, 30-item model (3 items for each modality). Findings from Study 2 supported the factor structure of a model containing 30 items loading into 10 modalities (i.e., unpleasant/pleasant emotions, confidence, anxiety, assertiveness, cognitive, bodily-somatic, motor-behavioral, operational, communicative, and social support). Convergent, discriminant, and nomological validity of the PESD-Sport was also demonstrated. Conclusion: Based on a substantive theoretical framework, this new measure of discrete emotions and performance-related experiences can advance the knowledge on the relationship between psychobiosocial states and performance. The scale could also inform applied interventions aimed at improving psychobiosocial experiences for performance enhancement. Graphical abstract: Image 1 Highlights: A new measure was developed to assess psychobiosocial experiences in sport. The Psychobiosocial Experience Semantic Differential scale in sport (PESD-Sport) contains 30 items. The 30 items load in 10 modalities of psychobiosocial experiences. Factorial and construct validity of the PESD-Sport was demonstrated.